PENGARUH KONSEP DIRI, TEMAN SEBAYA DAN BUDAYA KONTEMPORER TERHADAP PERILAKU KONSUMTIF SISWA SMP NEGERI 41 SURABAYA - Murwanti, Dwi (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to determine influence of self concept, peer group and contemporary culture by partial to consumptive behavior On the students of Junior High Schools 41 Surabaya, and The influence of self concept, peer group and contemporary culture jointly to consumptive behavior of students at Junior High Schools 41 in Surabaya. This study was a correlational research and using quantitative approach. Questionnaire technique  used to collect data with research object in SMP Negeri 41 Surabaya. Sample determination research use simple random sampling technique as much as 291 students of VII, VIII and IX class from total population of 1070 students. Technique analyze data is using multiple regression analysis. Based on data analysis can be concluded that:  The self concept itself have a significant effect on consumptive behavior, indicated that the stroneg self concept tendency consumptive behavior also increase if there is a conflict. Peers also has a significant effect on consumptive behavior, due to the friendship. Contemporary culture also has a significant effect on consumptive behavior it is because of a conflict so that the concept of a strong self could be affected on consumptive behavior, as well as peer and contemporary. The concept of self, peer and contemporary culture jointly give a significant effect on consumptive behavior, it is because of a conflict so that the  strong self concept could be affected on consumptive behavior, as well as peer and contemporary culture